Analysis of factors affecting student discipline and ethics at MAS YPP Sukamiskin - Ulfiah, Ade Resmi; Rochim, Akbar Alfito; Lestari, Afifah Fauzi; Sabrina, Ani; Setiaji, Aji (Educenter : Jurnal Ilmiah Pendidikan, 2024)
This research aims to analyze the factors of discipline and ethics at MAS YPP Sukamiskin, which are relatively low, and ultimately provide solutions to the issues raised. It is hoped that this research will be beneficial for all parties in improving the discipline and ethics of every student at MAS YPP Sukamiskin. This study uses a quantitative method with a descriptive approach. Data were collected directly from 79 respondents who are students of MAS YPP Sukamiskin. Based on the research results, it was found that the level of student discipline is most influenced by the firmness of rules factor, contributing the highest variance of 24.616%. This includes three variables: sanctions with a loading factor of 0.902, security personnel with a value of 0.855, and the implementation of rules and regulations with a loading factor of 0.640. Additionally, the level of student ethics is most influenced by the education and morals instilled by parents, whether in the school environment, family environment, or community environment, contributing the highest variance of 22.509%. This includes four variables: moral and religious education with a loading factor of 0.838, the role of teachers and the principal with a loading factor of 0.661, the role of religious figures with a loading factor of 0.720, and the role of parents with a loading factor of 0.654.